Monetary Policy Rules for Financially Vulnerable Economies - Moron, Eduardo (IMF Working Papers; Working Paper ;, 2003)
One distinguishable characteristic of emerging market economies is that they are not financially robust. These economies are incapable of smoothing out large external shocks, as sudden capital outflows imply large and abrupt swings in the real exchange rate. Using a small open-economy model, this paper examines alternative monetary policy rules for economies with different degrees of liability dollarization. The paper answers the question of how efficient it is to use inflation targeting under high liability dollarization. Our findings suggest that it might be optimal to follow a nonlinear policy rule that defends the real exchange rate in a financially vulnerable economy.